La brebis égarée et les sanglants pasteurs - Mathilde Bernard (Chrétiens et Sociétés, 2023)
This article, which is the result of a previous foray into the Lavallée collection of the Catholic University of Lyon’s library, aims to offer a look at the confessional controversy in the region of Nîmes at the turn of the 16th and 17th centuries. The writings of Guillaume Reboul, who converted to Catholicism under the influence of the Père Cotton, though they react to the rejection of his former community, are violently ironic and seem to be the mark of a pamphleteer's pen that is not about to dry up, or at least of a fruitful literary persona. G. Reboul is dangerous because he knows well his opponent and he is also dangerous because he appreciates oratorical jousting. These are the issues that seem to emerge from the study of his Salmonées. But what is also interesting about the few books that can actually be attributed to him with certainty is that they contribute to maintaining a fierce combat and to insinuating an oratorical style and literary references into the controversial enterprise. This aspect will develop into palimpsests of the Satyre Ménippée du Catholicon d’Espagne or of the Quart Livre in the apocryphal works, constituting the "Reboul corpus".